PENGEMBANGAN GAME EDUCATION PEMBELAJARAN PKn MATERI MENGHARGAI KEPUTUSAN BERSAMA KELAS V SD (Universitas Negeri Semarang, 2016)
Civic Education is not optime yet to used supported, until the students focus less and learning outcome still low until necessary a development of the game media education on the instructional Civic Education, so this research goal was examine the effectiveness of game media education on the instruction of Civic Education. The research was the Research and Development. The research taking place at the fifth grade of elementary school Ngaliyan 01. Expert assessment results indicate that game media education decent for test material, media, and language of experts. The percentage of the component assessment of content eligibility was 97,5% with category was very feasible, the component assessment of the representation was 90% with category was very feasible, and the component assessment of literary was 97,5% with category was very feasible. Activities of students obtain a score with a percentage of 85,5% in first meeting and 90,8% in second meeting with the criteria of students’ activity was very high. The conclusions of this research were game media education on Civic Education instructional was feasible and effective to used for instructional and improve student activity at respect the joint decision of Civic Education at fifth grade state elementary school Ngaliyan 01 Semarang city.